First-year cover crop effects on the physical and hydraulic properties of the surface layer in a loamy soil - Villarreal, Rafael (2021)
Soil degradation is a global problem, threating its conservation and affecting agronomic production. No-tillage (NT) is the main management system for soil conservation world-wide. However, in Argentina, simplification of the crop sequence with high proportion of soybean under NT is a very common practice, leading to soil physical constrains. Crop sequence intensification through the inclusion of cover crops has been reported as an effective tool in the long-term for the enhancement of ecosystems services, improving NT performance. The objective of this work was to follow the evolution of the structural pore domain in the surface layer during the first year after the incorporation of cover crop (cover fallow of barley (Hordeum vulgare L.) and vetch (Vicia sp. L.), CF), as compared with bare fallow (BF), under NT management in a field experiment located in the Argentinean Depressed Pampas Region. Mini-infiltration and evaporation experiments were conducted in undisturbed soil samples (0-5 cm depth) in the laboratory in order to determine the pore size distribution (PoSD) and hydraulic conductivity (K (h)) functions in three different dates (after cover crop seeding, after maize seeding and before maize harvest) in order to follow the changes in soil pore functioning during the first year of cover cropping management. Changes in the soil pore functioning were observed in the short-term after the first cover crop cycle, showing the time-dependence of the hydraulic soil properties. These changes were mainly observed during the maize cycle. Under CF an increment of structural porosity (PS) was observed at the end of the maize crop cycle, while during the fallow period this variable remained relatively constant. K (h) and structural porosity connectivity (Cw) showed a rapid increment under BF during the fallow period, while under CF the increase was more gradual, which could be related to pore clogging and roots decay cycles. From the obtained results, we found that the introduction of cover crops under NT promotes the increment of a secondary pore system related to structural soil porosity during the first year and enhances the unsaturated hydraulic conductivity and pore connectivity, especially at the end of the summer crop cycle. Our results highlight the importance of including cover crops into the crop rotation to improve the structural porosity and its connectivity. As well, the results show the necessity of including the short-term changes in the study of soil hydraulics properties.